Influence of surface coal mining on carbon storage in semi-arid steppe - Zhenhua Wu; Qiao Yu (Scientific Reports)
Abstract Clarifying the impact of surface coal mining on carbon storage in semi-arid steppe is an important means to promote low-carbon emission reduction and green high-quality development in semi-arid steppe surface coal mining area under the background of the “double carbon” goal. Based on the land use data of eight periods from 2002 to 2023, the carbon module of the InVEST model was used to estimate and analyze the spatiotemporal evolution characteristics of carbon storage in the mining area, and the impact of surface coal mining on the carbon sequestration capacity of semi-arid grassland ecosystem and the spatial differentiation of carbon storage were discussed. The results show that: (1) The total carbon storage in the study area showed a decreasing trend year by year, with a total decrease of 187.15 kiloton in 21 years, with an average annual decrease of 8.91 kiloton. The transformation from high carbon-density land to low carbon-density land weakened the carbon fixation function of the study area. (2) From 2002 to 2023, the carbon loss caused by mining in the study area was as high as 91.92 kiloton, with an average annual carbon loss of 4.38 kiloton, and the carbon sequestration capacity of the ecosystem was gradually degraded. (3) The carbon storage in the study area is dominated by insignificant change, accounting for 73% of the total area of the study area. The area with increased and decreased carbon storage accounts for 3.37% and 23.63% of the total area of the study area, respectively. This study can provide a reference for ecological restoration and planning of the “double carbon” target in surface coal mine areas.